Piecewise-continuous Riemann boundary-value problem on a rectifiable curve - Vasileva, Yu. V.; Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We extend classes of closed rectifiable Jordan curves and given functions in the theory of the piecewise-continuous Riemann boundary-value problem and the characteristic singular integral equation with Cauchy kernel related to this problem.